(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Analyzing customer engagement in social media marketing, particularly from the perspectives of women consumers, unveils intriguing insights into contemporary marketing strategies. Social media platforms have become pivotal in shaping consumer behavior, offering unique opportunities for brands to engage directly with their target demographics. Women, comprising a significant segment of social media users, present a nuanced perspective on how brands can effectively connect and resonate with their audience. This study tries to understand consumer behaviour and customer engagement in social media marketing. Understanding the dynamics of customer engagement begins with recognizing the multifaceted roles that social media plays in women’s lives. Platforms like Instagram, Pinterest, and Facebook serve not only as spaces for social interaction but also as arenas for inspiration, education, and self-expression. For women consumers, these platforms provide a forum to seek product recommendations, share experiences, and participate in communities centered around lifestyle choices, hobbies, and personal values. Effective engagement strategies in social media marketing often leverage storytelling and authenticity to establish meaningful connections. Brands that understand and align with women’s values, aspirations, and challenges can foster a sense of belonging and trust. Authenticity in content creation and communication resonates strongly with women consumers, who value transparency and genuineness in brand interactions. Analyzing customer engagement in social media marketing from the perspectives of women consumers underscores the importance of authenticity, visual appeal, and alignment with values. By embracing these insights, brands can forge meaningful connections, cultivate loyalty, and drive impactful outcomes in their social media marketing endeavors. Understanding and responding to the diverse needs and preferences of women consumers in the digital age is not just a strategic advantage but a pathway to sustainable growth and brand relevance in a competitive marketplace.